A Comprehensive Overview of Economic Zoology: Implications for Agriculture, Medicine, and Conservation - Nayan K. Prasad; Kumari Shachi (A Comprehensive Overview of Economic Zoology: Implications for Agriculture, Medicine, and Conservation, 2024)
"A Comprehensive Overview of Economic Zoology: Implications for Agriculture, Medicine, and Conservation " offers a comprehensive examination of the intricate relationship between zoological sciences and key sectors like agriculture, medicine, and conservation. This interdisciplinary exploration delves into the diverse roles of animals in these fields, from their impact on agricultural productivity to their significance in medical research and conservation efforts. Through a systematic analysis, the book elucidates the interconnections between ecological dynamics, animal biology, and human activities, emphasizing the crucial implications for sustainable development and biodiversity conservation. Key themes include the utilization of animals in pest management strategies, the discovery of medicinal compounds derived from diverse fauna, and the conservation challenges posed by human-animal interactions. By synthesizing research from various disciplines, this book serves as a valuable resource for scholars, practitioners, and policymakers seeking to understand and address the complex challenges at the intersection of economic zoology, agriculture, medicine, and conservation.